The King's Highway - James, G. P. R. (George Payne Rainsford), 1801?-1860 (Salt Lake City, UT : Project Gutenberg, 2003)
"The King's Highway" by G. P. R. James is a historical novel likely written in the early 19th century. The narrative opens on the Irish coast with a gathering of three characters$1 (Btwo men and a young boy$1 (Bentangled in a conversation that hints at a backdrop of political strife and personal turmoil, especially concerning a recent battle that has impacted their lives. At the start of the book, the atmosphere is tense as two men, one a soldier visibly affected by his experiences, and the other a more serious companion, discuss the aftermath of a military engagement, while a young boy, seemingly impacted by the somber mood, gazes toward the sea. The scene suggests themes of loss and sacrifice, especially regarding the death of a family member. The dialogue reveals underlying motives and relationships, hinting at plans and expectations, particularly concerning the boy$1 (Bs future amidst a tumultuous political landscape. The introduction sets the stage for a story involving conflict, loyalty, and the search for belonging. (This is an automatically generated summary.)s
Release date is 2003-02-01
This etext was produced by Jim Tinsley
Keywords: Great Britain -- History -- William and Mary, 1689-1702 -- Fiction